Pengujian Mekanik (Kekerasan dan Impact) Logam Ferro Valve Plat Double Dampers yang Digunakan Sebagai Penyaring Abu Boiler - Herry Darmadi; Arie Erza Erlangga Zebua; Nurul Shadrina Bintang; Agustin Nurya Savitri; Sorta Lumbantoruan (Program Pendidikan Vokasi Teknik Mesin, 2026)
Double damper also known as a double flap damper, is a special control device used in the ash transfer system of a boiler before it enters the multi-cyclone. Mechanical testing (hardness and impact) is the most effective test for obtaining an overview of the mechanical properties of a material. Although hardness testing is only performed at a single point, or a specific area, the hardness value is quite valid in indicating the strength of a material. By conducting a hardness test, a material is easily classified as ductile or brittle. Impact testing is a test that uses rapid loading. In mechanical testing, there are differences in the type of load given to the material. Tensile testing, compression testing, and torsion testing are tests that use static loads. Meanwhile, impact testing uses dynamic loads. In rapid loading, also known as impact loading, a large energy absorption process occurs from the kinetic energy of a load that impacts the specimen. This energy absorption process will be converted into various responses in the material such as plastic deformation, isterisis effects, friction, and inertia effects. The purpose of this study is to determine the hardness value of the Double Dampers Valve Plate and to determine the strength of the Double Dampers Valve Plate through the impact test method. The test results obtained the hardness value of test material 1 (0°C) = 111.3 HRC, test material 2 (25°C) = 108.033 HRC, and test material 3 (100°C) = 103.9 HRC. In the impact test, the results of the impact strength analysis of test material 1 (0oC) = 0.215 Kg.m/mm2, test material 2 (25°C) =0.235 Kg.m/mm2, and test material 3 (100°C)= 0.255 Kg.m/mm2.